Identifying Predictors of Physical Abuse Evaluation of Injured Infants: Opportunities to Improve Recognition. Issue 12 (20th December 2021) - Eismann, Emily A.; Shapiro, Robert Allan; Makoroff, Kathi L.; Theuerling, Jack; Stephenson, Nicole; Duma, Elena M.; Fain, Emily T.; Frey, Theresa M.; Riney, Lauren C.; Thackeray, Jonathan D.
Abstract : Objectives: To identify predictors of physical abuse evaluation in infants younger than 6 months with visible injury and to determine the prevalence of occult fracture and intracranial hemorrhage in those evaluated. Methods: Infants 6.0 months or younger who presented with visible injury to a pediatric hospital-affiliated emergency department or urgent care between July 2013 and January 2017 were included. Potential predictors included sociodemographics, treatment site, provider, injury characteristics, and history. Outcome variables included completion of a radiographic skeletal survey and identification of fracture (suspected or occult) and intracranial hemorrhage. Results: Visible injury was identified in 378 infants, 47% of whom did not receive a skeletal survey. Of those with bruising, burns, or intraoral injuries, skeletal survey was less likely in patients 3 months or older, of black race, presenting to an urgent care or satellite location, evaluated by a non–pediatric emergency medicine-trained physician or nurse practitioner, or with a burn. Of these, 25% had an occult fracture, and 24% had intracranial hemorrhage. Occult fractures were also found in infants with apparently isolated abrasion/laceration (14%), subconjunctival hemorrhage (33%), and scalp hematoma/swelling (13%). Conclusions: About half of preambulatory infants with visible injury were not evaluated for physical abuse. Targeted education is recommended as provider experience and training influenced the likelihood of physical abuse evaluation. Occult fractures and intracranial hemorrhage were often found in infants presenting with seemingly isolated "minor" injuries. Physical abuse should be considered when any injury is identified in an infant younger than 6 months.